Prevalence and Antimicrobial Susceptibility Pattern of Enterobacteriaceae Isolated from Hospitals Wastewater - Muhammad Rizwan, Habib Ullah, Anjala Ayoub, Haris Abdul Rehman, Muhammad Umar, Aqsa Qurban, Muhammad Aslam, Usama, Maria Kausar, Aamna Syed, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Hospital wastewater (HWW) is bearing in mind the main root to proliferate multidrug-resistant among the Enterobacteriaceae family. Enterobacteriaceae is suited to be a considerable risk for antibiotic-resistant through CTX-M production which is observed as an important factor leading to multiple drug-resistant. Study Design: A total of 100 samples of HWW and community wastewater were collected aseptically. Samples were sub-cultured through basic, selective, and UTI Chrome agar. Place of the study: This research was conducted in the Postgraduate Research Laboratory of the Department of Microbiology, Government College University Faisalabad. Duration of the study: The duration of the study was started from September 2018 to May 2019. Methodology: Bacteria were identified based on cultural characteristics and different biochemical tests. Antimicrobial susceptibility testing was performed as per CLSI 2016 guidelines. The molecular characterization of the CTX-M was done bt PCR to present its association with multidrug-resistant. Results: Among the total 165 isolates, the predominant bacteria were E.coli (48.1%) followed by K. pneumonia (25.3%), Shigella species (8.0%), and P.aeruginosa (12.7%) from hospital wastewater while E.coli (30.3%) followed by K. pneumonia (32.6%), Shigella species (20.9%) and P.aeruginosa (11.6%) were isolated from community wastewater. The AST of CTX-M producers and Non-CTX-M producers was also compared to find the relation of CTX-M to multidrug-resistant. Tigecycline was observed as a predominant resistant (≥96%) antibiotic followed by meropenem (≥40%) against all isolated CTX-M producers. Conclusion: The conclusion represented the existence of MDR Enterobacteriaceae in untreated hospital wastewater. All efforts revealed realize the requisite that hospital wastewater should be treated with standard treatment plants before exposing it to community wastewater. Keywords: Hospital wastewater; Antibiotic Resistance genes; CTX-M producers; Urinary Tract Infection (UTI),Enterobacteriaceae